Characteristics of violent deaths in the autopsy material of the Pathology and Forensic Medicine Institute of the Military Medical Academy in Belgrade - Marinković, Nadica; Perković Vukčević, Nataša; Aleksić, Ivan (Vojnosanitetski pregled, 2025)
Background/Aim. Violent death is caused by external factors. The aim of this study was to determine certain characteristics of violent deaths in the autopsy material of the Pathology and Forensic Medicine Institute of the Military Medical Academy in Belgrade, Serbia. Methods. A retrospective study of autopsy reports from forensic autopsies performed from 2010 until 2019 at the Pathology and Forensic Medicine Institute identified certain characteristics of violent death. Results. Out of 2,763 forensic autopsies performed during that period, violent death was established in 43.68% of the deceased. The majority of those who died violently were men (73.73%). Violent death was most common in people aged 21–40 years (34.96%). The most dominant cause of violent death was mechanical injuries, followed by chemical and asphyxiation injuries, while physical injuries were the rarest. In 59.32% of violent death cases, toxicological analysis of blood and urine samples showed individual or combined presence of alcohol, drugs, and illegal substances. Conclusion. The presented results may be significant for taking measures that will prevent and reduce the number of violent deaths.